An evaluation of web-based homework (WBH) delivery systems: University of Sharjah Experience - Elmehdi, Hussein M (International Journal of Emerging Technologies in Learning (iJET), 2013)
The objective of this paper is to investigate the effectiveness of the Web-Based Homework (WBH) systems on the performance of University of Sharjah (UAE) students. We have investigated: 1) student perceptions and acceptability of WBH systems;2) compare the studentsâ?? performance in homework assignments conducted using WBH systems and conventional paper-based homework approaches. Among the students surveyed, 53% preferred WBH systems to the conventional paper-based approach. In addition, 57% of the students felt the WBH system helped them improve their performance in the course. It was also found that students scored higher in homework assignments delivered via the WBH system (by about 17%). The advantages brought by WBH systems appear to motivate students and help improve their performance. It was also found that studentsâ?? maturity plays an important role in accepting the WBH system, where it was evident freshmen college students strongly opposed the use of WBH systems.